Islam in focus - Islamic Propogation Centre (Birmingham : Islamic Propogation Centre [production company] ; Kuala Lumpur : SABA Islamic Media [distributor])
The topics that have been discussed : definition of prophet, relationship ingenuity of prophethood, relationships between miracles and prophethood, number of prophets in Qur'an and the obligation of Muslims in belive of prophethood
Host: Dr. Mohammad Hosney Dr
Speaker: Dr. Jamal Badawi
Keywords: Prophets, Pre-Islamic; Prophets in the Qur'an